Emphasize Aging: Teaching Lifespan Developmental Psychology From an Intersectional Perspective. (December 2020) - Keener, Emily
Instructors of lifespan developmental psychology courses are faced with the impossible task of covering the entire lifespan. As such, aging can get neglected. The current paper advocates for approaches that emphasize aging throughout the course. One way to emphasize aging in lifespan courses is to approach the course from an intersectional perspective. Intersectionality advocates for simultaneous consideration of multiply marginalized people. Encouraging intersectional discussions of developmental topics will enrich course discussions and students will develop the habit of critically evaluating the material. Indeed, intersectional perspectives are critical in nature. Simply examining the generalizability of concepts to intersecting subgroups leaves out examination of interlocking systems of oppression and topics of disadvantage and privilege. As such, the current paper provides suggestions for questioning whether developmental concepts and theories are complicit with forces of oppression and domination of older adults.